Penganggaran Berbasis Kinerja pada Dinas Perumahan, Kawasan Permukiman dan Pertanahan Kota Bekasi - Marissa Julia Zahra; Candradewini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The Bekasi City Government strives to achieve good governance through regular performance and program evaluations to ensure that each budget is utilized optimally, providing maximum benefits to the community, and supporting the achievement of strategic government targets. The Housing, Urban, and Land Affairs Department of Bekasi City (Disperkimtan Kota Bekasi) has the task of drafting policy and strategy documents, including handling drinking water management. The implementation of drinking water management is translated through the Water Supply System Management and Development Program (SPAM), which is implemented using performance-based budgeting. However, the implementation of this program has not been optimal. The purpose of this study is to describe the performance-based budgeting on the water supply system management and development program of the Housing, Urban, and Land Affairs Department of Bekasi City. This study uses the theory of the performance-based budgeting cycle (Bappenas in Hadiwijoyo and Anisa, 2019), which consists of eight stages: setting programs, setting activities or sub-activities, setting targets, setting types and quantities of inputs, calculating budgets with standard costs, implementing activities and accountability, and performance measurement. The study's findings show that the implementation of performance-based budgeting on the water supply system management and development program in the Housing, Urban, and Land Affairs Department of Bekasi City has not been optimal in the aspects of setting input types and quantities, implementing activities and spending, and performance measurement.